2021
DOI: 10.3390/cancers13071672
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Feedforward Loops Formed by Nuclear Receptor RORγ and Kinase PBK in mCRPC with Hyperactive AR Signaling

Abstract: Metastatic castration-resistant prostate cancer (mCRPC) is a highly aggressive disease with few therapeutic options. Hyperactive androgen receptor (AR) signaling plays a key role in CRPC progression. Previously, we identified RAR-related orphan receptor gamma (RORγ) as a novel key driver of AR gene overexpression and increased AR signaling. We report here that several RORγ antagonists/inverse agonists including XY018 and compound 31 were orally effective in potent inhibition of the growth of tumor models inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Our previous studies showed that RORγ is overexpressed and plays a crucial role in mCRPC tumors [25,27]. As demonstrated in our previous studies [25,27,28], small molecule antagonists (also known as inverse agonists) of RORγ such as XY018 or SR2211 potently inhibited the growth and survival of mCRPC cells (Figure 1a,b).…”
Section: Rorγ Antagonists Inhibit Mcrpc Cell Growth and Survival By D...supporting
confidence: 63%
See 1 more Smart Citation
“…Our previous studies showed that RORγ is overexpressed and plays a crucial role in mCRPC tumors [25,27]. As demonstrated in our previous studies [25,27,28], small molecule antagonists (also known as inverse agonists) of RORγ such as XY018 or SR2211 potently inhibited the growth and survival of mCRPC cells (Figure 1a,b).…”
Section: Rorγ Antagonists Inhibit Mcrpc Cell Growth and Survival By D...supporting
confidence: 63%
“…Our previous studies showed that RORγ is overexpressed and plays a crucial role in mCRPC tumors [25,27]. As demonstrated in our previous studies [25,27,28], small molecule antagonists (also known as inverse agonists) of RORγ such as XY018 or SR2211 potently inhibited the growth and survival of mCRPC cells (Figure 1a,b). Given that elevated cholesterol levels promote PCa cell growth and survival, we thus investigated whether the effect of RORγ inhibition is linked to its potential function in control of the increased cholesterol level in mCRPC.…”
Section: Rorγ Antagonists Inhibit Mcrpc Cell Growth and Survival By D...supporting
confidence: 63%
“…However, the mechanism has not been revealed. Moreover, PBK was a downstream target of RORγ that exerted the cellular effects, indicating that PBK , RORγ , and AR were all associated with the growth and survival of aggressive prostate cancer ( Zhang et al, 2021 ). However, possible mechanisms in non-aggressive prostate cancer have not been researched.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in search for alternative therapeutic targets for advanced cancer, RORγ in tumor cells was identified to play a critical role in tumor progression in certain types of cancer ( Zou et al, 2022a ), including castration-resistant prostate cancer (CRPC) ( Wang et al, 2016 ; Wang et al, 2020 ; Zheng et al, 2020 ; Zhang et al, 2021 ), triple-negative breast cancer (TNBC) ( Cai et al, 2019 ; Zou et al, 2022b ), small cell lung carcinoma (SCLC) ( Chen et al, 2022 ) and pancreatic ductal adenocarcinoma (PDAC) ( Lytle et al, 2019 ). In CRPC tumors and cells, RORγ directly activates androgen receptor (AR) expression and AR signaling ( Wang et al, 2016 ; Zheng et al, 2020 ; Zhang et al, 2021 ). In TNBC cells and tumors, RORγ acts as a master activator of tumor cholesterol biosynthesis program ( Cai et al, 2019 ; Zou et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%